Digital and analog communication systems - Couch, Leon W. (Upper Saddle River, New Jersey : Prentice-Hall, 2013)
Continuing the tradition of the first through the seventh editions of digital and analog communication systems, this eight edition provides the latest up-to-date treatment of digital communication systems.
Introduction -- Signals and Spectra -- Baseband Pulse and Digital Signaling -- Bandpass Signaling Principles and Circuits -- AM, FM, and Digital Modulated Systems -- Random Processes and Spectral Analysis -- Performance of Communication Systems Corrupted by Noise -- Wire and Wireless Communication Applications.
Includes bibliographical references and index.
Keywords: COMMUNICATION